The Ambivalence of the Supreme Court's Jurisprudence in Recognizing the Customary Rights of Indigenous Communities and Its Implications for the Transformation of the Concept of Communal Rights in National Land Law - Akh Mulyanto; Richard (Journal Customary Law, 2026)
This study's objective is to examine the Supreme Court's reluctance in acknowledging indigenous peoples' customary rights and its consequences for the evolution of the notion of communal rights in Indonesian national land law. However, the Supreme Court's jurisprudence exhibits an ambivalent tendency in judicial practice, where a formal evidentiary strategy that prioritizes land title certificates as the primary evidence in land disputes frequently limits the acceptance of customary law. On the other hand, the development of legislative policies that introduce the concept of communal rights as a form of recognition of land ownership by indigenous communities aims to provide legal certainty, but has the potential to reduce the dimension of customary authority contained in the concept of customary rights. In order to achieve agrarian justice for Indonesia's indigenous communities, it is necessary to reconstruct the paradigm of more substantive customary law recognition within the national land law system. This circumstance demonstrates how the dualism between state law and customary law in the land sector persists in a new form.